Guiding Networked Innovation Projects Towards Commercial Success—a Case Study of an EU Innovation Programme with Implications for Targeted Open Innovation - Jaekel, Martin; Wallin, Arto; Isomursu, Minna (Journal of the knowledge economy, 2015)
Due to demographic change, public research funds have been directed to boost development of ambient assisted living solutions. This effort has been expected to create a market for information and communications technology (ICT)-enhanced products and services, which could support older adults in living independently for longer. However, the market for such products and services has developed rather slowly despite strong public investment, and the uptake of the developed solutions has not always met the high expectations (Eberhardt et al. 2010); hence, it seems to be difficult to deliver on the promise that ICTs will help mitigate the economic and social impact of demographic ageing. Therefore, two urgent questions need to be answered to tap the full potential of new technologies in demographic ageing: (i) what are the problems of public-private partnerships (PPPs) in commercializing ICT solutions in silver markets and (ii) how to support PPPs through policy and other measures to succeed. In this paper, we address these questions by analysing the case study based on the Ambient Assisted Living Joint Programme (AAL JP), which has reinforced market orientation of collaborative research and innovation projects through various types of activities. The paper presents a framework that is based on an analysis of commercialization needs and requirements of European networked innovation projects funded by the AAL JP. The data set was collected during business development workshops with 50 different project consortia representing 117 individual partners notably including users, researchers, SMEs, third-sector organizations and industrial partners. The resulting support framework covers (1) what can be done in ensuring that projects are initiated in a way conducive to successful commercialization, (2) what can be done during the execution of the project to support commercialization activities, and (3) how can project participants be supported after the financially supported collaboration phase. The analysis of the networked innovation projects financed through the AAL JP is also discussed from the viewpoint of targeted open innovation with policy implications.